Apnea of prematurity: challenges and solutions - Picone S; Aufieri R; Paolillo P (Dove Medical Press, 2014)
Simonetta Picone, Roberto Aufieri, Piermichele PaolilloDivision of Neonatology and Neonatal Intensive Care, Department of Maternal and Child Health, Casilino General Hospital, Rome, ItalyAbstract: Apnea of prematurity is a developmental disorder that frequently affects preterm infants, especially those with lower gestational age. Even if apnea of prematurity is by definition a self-limiting condition, it can cause serious problems during the hospital stay and can potentially have long-term neurological and cognitive consequences depending on the severity and intensity of the episodes. The diagnosis of apnea of prematurity can be made only after excluding a number of diseases of the preterm infant in which apnea may be an epiphenomenon. Etiological diagnosis is essential for selection of appropriate treatment, which may be nonpharmacological or involve use of drugs.Keywords: apnea of prematurity, idiopathic and secondary apnea, caffeine